The Effect of Contextual Teaching and Learning Model Assisted by Video on Students' Learning Outcomes and Motivation - Sari, Ayu Ratna; Gummah, Syifa'ul; Syukroyanti, Baiq Azmi; Habibi, Habibi (Lensa: Jurnal Kependidikan Fisika, 2024)
This study explores the effectiveness of the Contextual Teaching and Learning (CTL) model, enhanced by video, in improving students' learning outcomes and motivation, specifically in understanding complex physics topics like sound waves. Traditional teaching methods often struggle to engage students with abstract content, creating a need for innovative approaches that bridge theory with practical applications. The CTL model aims to make learning more meaningful by connecting academic material with real-world contexts. A quasi-experimental design with a pretest-posttest control group was employed, involving two randomly selected groups from 50 students at SMAN 1 Masbagik. The experimental group was taught using the CTL model with video assistance, while the control group followed conventional methods. Data collection included learning outcome tests and motivation questionnaires, analyzed using normality, homogeneity, and t-tests to evaluate differences between groups. Results showed that the experimental group achieved a significantly higher posttest average score (78.92) than the control group (74.20), indicating improved comprehension. Additionally, motivation scores in the experimental group averaged 83.5, categorized as "motivated," suggesting increased engagement. The t-test confirmed a statistically significant difference in learning outcomes, underscoring the effectiveness of video-assisted CTL in enhancing both comprehension and motivation. These findings support the integration of video within the CTL model as a valuable educational strategy to create a more interactive, engaging, and effective learning environment. This study offers insights into how technology-enhanced teaching models can address the challenges of modern education and better prepare students for real-world problem-solving.